Feasibility of cross-calibrating ocean-color sensors in polar orbit using an intermediary geostationary sensor of reference - Tan, Jing; Frouin, Robert; Murakami, Hiroshi (Frontiers in Remote Sensing, 2023)
A generic methodology is presented to cross-calibrate satellite ocean-color sensors in polar orbit using an intermediary geostationary sensor of reference. In this study, a geostationary sensor, i.e., AHI onboard Hiwamari-8, is used as the intermediary sensor to cross-calibrate SGLI onboard GCOM-C and MODIS onboard Terra and Aqua (MODIS-A and MODIS-T) after system vicarious calibration (SVC). Numerous coincidences were obtained near the Equator using three days of imagery, i.e., 11 May 2018, 22 January 2019, and 25 January 2020. Spectral matching to AHI spectral bands was first performed for a wide range of angular geometry and aerosol conditions using a single band or multiple bands of SGLI, MODIS-A and MODIS-T, yielding root mean square differences of 0.1 to 0.7% in the blue and green and 0.7 to 3.7% in the red depending on the band combination. Limited by the inherent AHI instrument noise and the system vicarious calibration of individual polar-orbiting sensors, cross-calibration was only performed for equivalent AHI bands centered on at 471, 510, and 639 nm. Results show that MODIS-A and MODIS-T are accurately cross-calibrated, with cross-calibration ratios differing by 0.1 to 0.8% in magnitude. These differences are within or close to the estimated uncertainties of ±0.6 to ±1.0%. In contrast, SGLI shows larger cross-calibration differences, i.e., 1.4, 3.4, and 1.1% with MODIS-A and 1.5, 4.6, and 1.5% with MODIS-T, respectively. These differences are above uncertainties of ±0.8-1.0% at 471 and 510 nm and within uncertainties of ±2.3 and ±1.9% at 639 nm. Such differences may introduce significant discrepancies between ocean-color products generated from SGLI and MODIS data, although some compensation may occur because different atmospheric correction schemes are used to process SGLI and MODIS imagery, and SVC is based on the selected scheme. Geostationary sensors with ocean color capability have potential to improve the spectral matching and reduce uncertainties, as long as they provide imagery at sufficient cadence over equatorial regions. The methodology is applicable to polar-orbiting optical sensors in general and can be implemented operationally to ensure consistency of products generated by individual sensors in establishing long-term data records for climate studies.